Ojibwe singers : hymns, grief, and a native culture in motion - McNally, Michael David (Religion in America series (Oxford University Press), 2000)
The Ojibwe of Anishinaabe are a native American people who were taught by 19th-century missionaries to sing evangelical hymns translated into the native language both as a means of worship and as a tool for eradicating the ""indianness"" of the native people. Rather than Americanizing the people, however, these songs have become emblematic of Anishinaabe identity. In this book, Michael McNally uses the Ojiwbe's hymn-singing as a lens to examine how this native American people has creatively drawn on the resources of ritual to negotiate identity and survival within the structures of colonialism